The Importance of Leadership Development in Medical Curricula: A UK Perspective (Stars are Aligning) - Till A; McKimm J; Swanwick T (Dove Medical Press, 2020)
Alex Till, 1 Judy McKimm, 2 Tim Swanwick 3 1School of Psychiatry, Health Education England (North West), Manchester, UK; 2Swansea Medical School, Swansea, UK; 3NHS Leadership Academy, Leeds, UKCorrespondence: Alex TillSpecialty Registrar in Forensic Psychiatry, Health Education England (North West), Manchester M1 3BN, UKEmail alextill54@gmail.comAbstract: “Medical leadership and management” describes the engagement of doctors in the leadership and management of both individual patient care and of the departments, organizations and systems within which they work. Around the world, doctors are generally accepted as the leaders of clinical teams, holding ultimate accountability for individual patient care. However, the role of doctors as organizational and system leaders within healthcare, despite evidence of benefit, shows considerable variation. In this article, we briefly explore the history of leadership development for doctors, and then, taking a UK perspective on recent developments in undergraduate education and postgraduate training, consider the opportunities and challenges for medical schools, educators and doctors in implementing these. The future of medical leadership and management development is promising although there is still a lack of evidence on the longer-term outcomes and impact on patients of current interventions. It is clear, however, that faculty need to be skilled in holding effective developmental conversations and structuring formative experiences for those they educate, and that leadership development must be integrated longitudinally throughout a doctor’s career, with undergraduate development being a critical stage for helping medical students recognize and understand their wider responsibility to the system, as well as the patient in front of them.Keywords: leadership, leadership development, medical school, UK, curriculum, undergraduate